2016
DOI: 10.3233/ves-160583
|View full text |Cite
|
Sign up to set email alerts
|

Posturographic profile of patients with persistent postural-perceptual dizziness on the sensory organization test

Abstract: Patients with PPPD had difficulties with postural control across multiple sensory challenges, consistent with postulated neurophysiologic mechanisms of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
1
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 26 publications
7
44
1
14
Order By: Relevance
“…Research on the four predecessors of PPPD 13,19,20,[24][25][26][27][28][29][30][31][32] provided hypotheses about its pathophysiological mechanisms that have been supported and extended by rapidly emerging data from investigations into PPPD itself. 16,[33][34][35] In past and present studies, 13,16,19,[24][25][26] psychological factors have been shown to play distinct roles in the development of PPPD, but importantly, these factors are not present in all patients, and their existence does not indicate that PPPD is a psychiatric disorder. 1 ►Fig.…”
Section: Putative Pathophysiological Mechanisms Of Pppdmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on the four predecessors of PPPD 13,19,20,[24][25][26][27][28][29][30][31][32] provided hypotheses about its pathophysiological mechanisms that have been supported and extended by rapidly emerging data from investigations into PPPD itself. 16,[33][34][35] In past and present studies, 13,16,19,[24][25][26] psychological factors have been shown to play distinct roles in the development of PPPD, but importantly, these factors are not present in all patients, and their existence does not indicate that PPPD is a psychiatric disorder. 1 ►Fig.…”
Section: Putative Pathophysiological Mechanisms Of Pppdmentioning
confidence: 99%
“…Physiological, psychological, and advanced brain imaging studies published since that time have supported this conceptualization. 16,[33][34][35][36][37][38][39][40] As discussed earlier and shown on the left side of ►Fig. 2, PPPD may be triggered by neuro-otologic disorders, other structural or metabolic conditions, and psychological distress that cause vertigo, unsteadiness, or dizziness, or disrupt balance function.…”
Section: Putative Pathophysiological Mechanisms Of Pppdmentioning
confidence: 99%
See 1 more Smart Citation
“…A tontura relatada por 30% dos entrevistados (Figura 4) é uma patologia que faz com que o indivíduo tenha uma falsa sensação de movimento do ambiente que o rodeia, ou de si mesmo; além dessa péssima sensação, a tontura também causa desequilíbrio e sensação de enjoo (SÖHSTEN et al, 2016). Os achados dos estudos desenvolvidos por Bittar e Sohsten (2015) em pacientes com tontura mostram relação intrínseca com a exposição à poluição sonora.…”
Section: Resultsunclassified
“…Положительный эффект продемонстрировало сочетание психотерапии с методиками вестибулярной реабилитации на стабилографической платформе с биологической обратной связью (БОС). Данные постурографии свидетельствуют о трудностях постурального контроля при множественных сенсорных стимулах у пациентов с ПППД, что указывает на нарушение адаптивных реакций системы поддержания равновесия у данной категории больных [24]. Программы реабилитации на стабилографической платформе с БОС включают в себя упражнения на габитуацию и адаптацию.…”
Section: л е ч е н и еunclassified